2018
DOI: 10.1002/uog.18908
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of preterm birth with pessary in singletons (PoPPS): randomized controlled trial

Abstract: Cervical pessary use was not associated with prevention of PTB in women with a singleton pregnancy, short CL on TVS and no prior sPTB in this small, underpowered randomized controlled trial. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 16 publications
0
46
0
2
Order By: Relevance
“…HIV serostatus has not been assessed as a cofactor in other studies of short cervix, likely because most have been performed in countries where HIV is rare. Prevalence estimates of short cervix have ranged between 1.7% and 2.4% in US and UK trials, compared with 3.3% in our study, although most other studies limit their data to cervical lengths assessed prior to 24 weeks of pregnancy. A higher prevalence of short cervix may also be explained at least partly by self‐selection of higher‐risk women into a prenatal cohort study whose aim is to investigate the predictors of PTB.…”
Section: Discussionmentioning
confidence: 99%
“…HIV serostatus has not been assessed as a cofactor in other studies of short cervix, likely because most have been performed in countries where HIV is rare. Prevalence estimates of short cervix have ranged between 1.7% and 2.4% in US and UK trials, compared with 3.3% in our study, although most other studies limit their data to cervical lengths assessed prior to 24 weeks of pregnancy. A higher prevalence of short cervix may also be explained at least partly by self‐selection of higher‐risk women into a prenatal cohort study whose aim is to investigate the predictors of PTB.…”
Section: Discussionmentioning
confidence: 99%
“…This is a planned secondary analysis of the Prevention of Preterm birth with Pessary in Singletons trial (PoPPS trial) which was aimed to determine if pessary use prevents preterm birth in singleton gestations with a short TVU CL and without a prior spontaneous preterm birth . The parent trial was Institutional Review Board approved and only de‐identified data were used in this secondary analysis.…”
Section: Methodsmentioning
confidence: 99%
“…After randomization the women involved in the study underwent a physical manual cervical exam to assess the Bishop score from which cervical dilation was assessed for this secondary analysis. As part of the Bishop score, cervical dilation of the internal os was assigned a value 0‐2, with 0 = closed, 1 = 1‐2 cm dilated, and 2 = 3‐4 cm dilated . Physical exam was performed by selected investigators trained in pessary placement and standardized reporting of cervical exam; examiners were not blinded to the CL result and exam was performed after ultrasound and prior to any treatment initiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in this issue considers the value of pessary placement in low-risk singleton pregnancy (without prior preterm birth). In 122 women with cervical length < 20 mm, those who received a pessary were no more likely to deliver preterm than were those who did not (43% vs 40%; relative risk, 1.09 (95% CI, 0.71-1.68)) 7 . This study confirms that women with a short cervix are at high risk of early delivery but is at variance with other recent low-risk studies suggesting substantial benefit of pessary use 8 .…”
Section: An Economic Evaluation In This Issue Demonstrates Cost Savmentioning
confidence: 97%